Gorlin-Goltz syndrome in an older black adult. Case Report - Mauricio Andrés Uribe-Valencia; Janeth Jurado-Delgado; Lina Marcela Velásquez-Tafur; Luis Fernando Cárdenas-Cardona (Revista de la Facultad de Medicina)
Introduction: Gorlin-Goltz syndrome (GGS), or basal cell nevus syndrome (BCNS), is a rare genetic disease that induces the development of odontogenic keratocysts, skeletal malformations and neoplasms, especially multiple and recurrent basal cell carcinomas (BCC). This condition is rare in black people, being reported in this population in only 5% of the cases.